2017
DOI: 10.1021/acscatal.7b03367
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Based Catalytic System for the Synthesis of Bio-Derived Cyclic Carbonates under Mild Conditions

Abstract: Recently, bio-derived cyclic carbonates have gained significant importance: e.g., as building blocks in non-isocyanate polyurethanes (NIPUs). Herein we report the development of a calcium-based catalyst system for the synthesis of challenging internal and trisubstituted cyclic carbonates from bio-derived epoxides and CO2 under mild reaction conditions. Several crown ethers were tested as ligands in combination with various cocatalysts for the possible activation of CO2. The most active system consists of a dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 89 publications
(135 reference statements)
1
113
0
3
Order By: Relevance
“…[2,3] Compared to carbon capture and storage( CCS) techniques, carbon capturea nd utilization (CCU) techniques are more attractive, ast he captured CO 2 can be effectively converted to various valuable productss uch as urethanes, formic acid, dimethyl carbonate, and cyclic carbonates. [11][12][13][14][15][16][17][18][19][20] Cyclic carbonates are highly stable compounds; thus, long-term sequestration of CO 2 is possible. [11][12][13][14][15][16][17][18][19][20] Cyclic carbonates are highly stable compounds; thus, long-term sequestration of CO 2 is possible.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Compared to carbon capture and storage( CCS) techniques, carbon capturea nd utilization (CCU) techniques are more attractive, ast he captured CO 2 can be effectively converted to various valuable productss uch as urethanes, formic acid, dimethyl carbonate, and cyclic carbonates. [11][12][13][14][15][16][17][18][19][20] Cyclic carbonates are highly stable compounds; thus, long-term sequestration of CO 2 is possible. [11][12][13][14][15][16][17][18][19][20] Cyclic carbonates are highly stable compounds; thus, long-term sequestration of CO 2 is possible.…”
Section: Introductionmentioning
confidence: 99%
“…[1c] Unfunctionalized saturated carbonates can be used for the synthesis of polymers by nucleophilic ring opening with diamines leading to bis-hydroxycarbamates as starting materials for isocyanatefree polyester polyurethanes. [53] 1c can be formed asab yproduct of back-biting in CHO/CO 2 copolymerization. In general,p olymers with relativelyl ow molecular weights wereo btained at high temperature with partial loss of CO 2 .…”
Section: Unfunctionalized Cyclic Carbonatesmentioning
confidence: 99%
“…[211] Improvement of the keyc atalytic step of CO 2 cycloaddition to the epoxide precursors is another viable strategy to further enhancet he sustainability of 5CCs. Additionally,e fficient Lewis acids have emerged for the insertion of CO 2 into internal epoxides.F or instance, the organometallic complexes shown in Scheme 24 allow the efficient carbonation of internal epoxides such as limonene (7a, 9) [65a, 164] and epoxidized fatty acids (7b, 8) [53,214] at moderateC O 2 pressures. [212] These compounds generallyr equire temperatures around1 00 8C, pressures in the 20-40 bar range, and polar solvents such as DMF or NMP (for LiBr), leadingt om ore demanding purification procedures and to the production of chemical wastes.…”
Section: Synthesis Of Sustainable 5cc Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…As a continuation of our study on using ligands for enhancing the coupling reaction, and encouraged by the Werner group's work, which depicted that catalyst system ‘CaI 2 /L1’ (or ‘CaI 2 /18‐crown‐6’) could be used for the synthesis of cyclic carbonates from epoxides and CO 2 (Scheme , a and b), we tried the reaction in the presence of different ligands, and found that the combination of ‘CoNO 3 . 6H 2 O/L2’ could efficiently promote the coupling reaction of CO 2 and epoxides in solvent‐free reactions (Scheme , c).…”
Section: Introductionmentioning
confidence: 99%